Foreign rule and its executive power (An analytical study) - Karim, ِAsst.L. Tehran Mohammad (Sulaimani Journal for Humanities, 2026)
This research examines the conditions and procedures for enforcing foreign court judgments in Iraq, highlighting the balance between the requirements of national sovereignty and the necessities of international judicial cooperation. The study aims to clarify the nature of a foreign judgment, the methods used to grant it executory force, and its legal implications as a res judicata or as evidence. The research employs both analytical and descriptive methodologies to assess the position of the Iraqi legislator in Law No. (30) of 1928 and applicable international agreements. The study concludes that Iraq adopts the "execution order" system through limited oversight that focuses solely on fulfilling legal requirements without reviewing the merits of the dispute. The research concludes by emphasizing the need for the Iraqi legislature to enact modern and comprehensive legislation that keeps pace with developments in private international transactions.
Keywords: Foreign rule; executive power; national sovereignty; judicial cooperation; enforcement order action; Iraqi private international law